A new method to detect and classify polar stratospheric nitric acid trihydrate clouds derived from radiative transfer simulations and its first application to airborne infrared limb emission observations - Kalicinsky, Christoph; Griessbach, Sabine; Spang, Reinhold (Atmospheric Measurement Techniques, 2021)
Polar stratospheric clouds (PSCs) play an important role in the spatial and temporal evolution of trace gases inside the polar vortex due to different processes, such as chlorine activation and NOy redistribution. As there are still uncertainties in the representation of PSCs in model simulations, detailed observations of PSCs and information on their type – nitric acid trihydrate (NAT), supercooled ternary solution (STS), and ice – are desirable. The measurements inside PSCs made by the CRISTA-NF (CRyogenic Infrared Spectrometers and Telescope for the Atmosphere – New Frontiers) airborne infrared limb sounder during the RECONCILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) aircraft campaign showed a spectral peak at about 816 cm−1. This peak is shifted compared with the known peak at about 820 cm−1, which is recognised as being caused by the emission of radiation by small NAT particles. To investigate the reason for this spectral difference, we performed a large set of radiative transfer simulations of infrared limb emission spectra in the presence of various PSCs (NAT, STS, ice, and mixtures) for the airborne viewing geometry of CRISTA-NF. NAT particles can cause different spectral features in the 810–820 cm−1 region. The simulation results show that the appearance of the feature changes with an increasing median radius of the NAT particle size distribution, from a peak at 820 cm−1 to a shifted peak and, finally, to a step-like feature in the spectrum, caused by the increasing contribution of scattering to the total extinction. Based on the appearance of the spectral feature, we defined different colour indices to detect PSCs containing NAT particles and to subgroup them into three size regimes under the assumption of spherical particles: small NAT (≤ 1.0 µm), medium NAT (1.5–4.0 µm), and large NAT (≥ 3.5 µm). Furthermore, we developed a method to detect the bottom altitude of a cloud by using the cloud index ...